Pleural Disease 2020
DOI: 10.1183/2312508x.10023719
|View full text |Cite
|
Sign up to set email alerts
|

Pleural infection: moving from treatment to prevention

Abstract: Pleural infection incidence is on the rise. Many unknowns remain with regard to the etiopathogenesis of this condition. Risk stratification at the front door and early aggressive treatment by specialist teams could help improve outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 113 publications
(149 reference statements)
0
6
0
1
Order By: Relevance
“…Despite this, a large retrospective population-based observation study demonstrated much higher levels of mortality for patients managed non-operatively, even after adjusting for differences in age and comorbidity (11.1% 30-day mortality vs 3.3%), and this finding is supported by other retrospective studies [101][102][103]. What is clear, however, is the distinct lack of head-to-head, prospective data to settle this debate [19,26]. Even a recent Cochrane review into the question could only produce 8 trials across 391 participants, of which 6 trials were within a paediatric population.…”
Section: Surgerymentioning
confidence: 95%
See 2 more Smart Citations
“…Despite this, a large retrospective population-based observation study demonstrated much higher levels of mortality for patients managed non-operatively, even after adjusting for differences in age and comorbidity (11.1% 30-day mortality vs 3.3%), and this finding is supported by other retrospective studies [101][102][103]. What is clear, however, is the distinct lack of head-to-head, prospective data to settle this debate [19,26]. Even a recent Cochrane review into the question could only produce 8 trials across 391 participants, of which 6 trials were within a paediatric population.…”
Section: Surgerymentioning
confidence: 95%
“…In a recent systematic review encompassing 75 studies and more than 10,000 participants, Staphylococcus aureus (20.7%) appears to have overtaken the Streptococcus viridans group (18%) as the most commonly cultured pathogen globally [18]. Hitherto, Streptococcus milleri, the most common subgroup of S. viridans, was thought to be the commonest isolate [6,19]. While the tropics and temperate regions had a greater incidence of Gram-positive organisms, subtropical regions had a higher incidence of Gram-negative bacteria.…”
Section: Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nick A. Maskell 1 , Christian B. Laursen 2,3 , Y.C. Gary Lee 4,5 and Najib M. Rahman 6,7,8,9 @ERSpublications Pleural diseases are common and associated with specialist procedures and a growing evidence base. This book, written by experts in the field, summarises up-to-date knowledge of the investigation, management and future directions of this exciting field.…”
Section: Introductionmentioning
confidence: 99%
“…The Monograph therefore covers aspects of background and investigation, including epidemiology [1], physiology and its relationship to symptoms and management [2], basic science and animal models of pleural disease [3], the role of radiology [4] and ultrasound [5], which is now considered an essential tool for pleural disease management. We have also included chapters on the major pleural entities including pleural infection [6], MPE [7], mesothelioma [8], pneumothorax [9], TB [10] and non-specific pleuritis [11]. Finally, liaison with other specialities and delivery of a pleural service has been addressed through chapters on surgery for pleural disease [12] and the key components of an active pleural service [13].…”
Section: Introductionmentioning
confidence: 99%